Hydrogel high polymer material containing active molecules and preparation method thereof

By polymerizing active small molecules in the wet and soft confined space of the hydrogel, combined with fluorescence effect monitoring technology, the problem of insufficient understanding of the microstructure and morphology of polymers in the hydrogel is solved, and efficient polymerization reaction control is achieved. Form a polymer material with excellent properties.

CN119463169APending Publication Date: 2025-02-18DEZHOU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411349465.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing technology lacks effective research methods on the polymerization process of active small molecules in the wet and soft confined space of hydrogels, resulting in insufficient understanding of the microstructure and morphology of polymers in hydrogels, as well as the polymerization process for hydrogels. Research gaps in the impact of internal network structure.

Method used

By preparing a hydrogel polymer material containing active molecules, using raw materials such as polyvinyl alcohol, para-phenylenediamine, ammonium persulfate and hydrochloric acid to form a three-dimensional network structure of the hydrogel, and monitoring the polymerization reaction through fluorescence effect. The polymer degree and content of polymer are determined.

Benefits of technology

Real-time monitoring and visualization of the polymerization process of active small molecules in the wet and soft confined space of the hydrogel is achieved, which significantly improves the understanding of the polymerization reaction mechanism and forms polymer materials with excellent mechanical properties and conductive properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463169A_ABST
    Figure CN119463169A_ABST
Patent Text Reader

Abstract

The invention relates to the field of functional polymer materials, and discloses a hydrogel polymer material containing active molecules, which comprises 4.5%-6.5% of polyvinyl alcohol, 85.5%-90.5% of deionized water, 7%-10% of p-phenylenediamine, 1%-3% of ammonium persulfate and 2%-5% of hydrochloric acid. The real-time monitoring and visualization of the polymerization process of the active molecules in the hydrogel are realized by utilizing the fluorescence effect and aggregation-induced effect of the active molecules, the understanding of the polymerization reaction mechanism is improved, the performance regulation and control range of the hydrogel material is expanded by regulating and controlling the polymerization reaction and accurately controlling the microstructure of the polymer, and in addition, the application prospect is wide. Active small molecules are orderly polymerized in a hydrogel confinement space to form a high polymer material with excellent performance, the poly-p-phenylenediamine hydrogel material has application prospects in multiple fields and shows good physical and chemical properties and biocompatibility, and the hydrogel prepared by adopting a freeze-thaw method is simple in process, suitable for large-scale production and suitable for industrial production. And the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of functional polymer materials, in particular to a hydrogel polymer material containing active molecules and a preparation method thereof. Background Art

[0002] In recent years, the polymerization reaction of active small molecules in confined spaces has become an important method for preparing functional polymer materials and has been widely used in nanoscale research. For example, Liu Ying's team at the Chinese Academy of Sciences prepared a nanocapsule palladium catalyst with a confined reaction environment. By regulating its size range, they deeply explored the relationship between the catalyst structure and the structure of the olefin polymer product. Similarly, Xiang Zhonghua's team at Beijing University of Chemical Technology used three-dimensional metal-organic frameworks (MOFs), two-dimensional layered montmorillonite and zero-dimensional mesoporous silica as nano-confined spaces to significantly improve the distribution density and catalytic activity of active centers in catalytic materials. Jiang Tao's team at Tianjin University of Science and Technology improved the activity of ethylene polymerization and the selectivity for 1-octene products through the "confined nanospace effect" in the nanopores of molecular sieves. In these studies, the polymerization mechanism of active small molecules in nanospace and its influencing factors have been relatively fully explained and understood.

[0003] Hydrogels are a class of materials composed of highly cross-linked three-dimensional network structures. Due to their rich water content and unique network structure, they can absorb and retain large amounts of water, allowing them to swell in water without dissolving. The three-dimensional network structure of hydrogels can be isotropic or anisotropic, and may exhibit features such as through-hole structures or lamellar structures. Due to these different internal structures, hydrogels provide confined soft and wet spaces for the transfer and polymerization of mediators or small molecules. However, current research mainly focuses on the confined space at the nanoscale, and there is still a lack of effective research methods for the polymerization process of active small molecules in the soft and wet confined space of hydrogels. This has led to a lack of understanding of the microstructure and morphology of polymers within hydrogels, as well as a research gap in the impact of the polymerization process on the internal network structure of hydrogels.

[0004] To solve the above problems, the present invention proposes a hydrogel polymer material containing active molecules and a preparation method thereof to address the deficiencies of the prior art. Summary of the Invention

[0005] In response to the shortcomings of the existing technology, the present invention provides a hydrogel polymer material containing active molecules and a preparation method thereof, aiming to solve the problem of lack of effective means to study the polymerization process of active small molecules in a wet and soft confined space, especially the insufficient understanding of the microstructure and morphology of the polymer inside the hydrogel, and the research gap in the impact of the polymerization process on the internal network structure of the hydrogel.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: a hydrogel polymer material containing active molecules, the hydrogel is composed of the following raw materials in the following weight percentage ranges:

[0007] Polyvinyl alcohol: 4.5%-6.5%,

[0008] Deionized water: 85.5%-90.5%,

[0009] p-phenylenediamine: 7%-10%,

[0010] Ammonium persulfate: 1%-3%,

[0011] Hydrochloric acid: 2%-5%.

[0012] This formula combination ensures the formation of the hydrogel and the effective polymerization of active molecules through the rational proportions of polyvinyl alcohol, p-phenylenediamine, ammonium persulfate, and hydrochloric acid. Polyvinyl alcohol, as the matrix material, provides the hydrogel's three-dimensional network structure, giving the hydrogel good mechanical properties and water absorption. p-phenylenediamine, as the active molecular monomer, undergoes polymerization under the catalysis of ammonium persulfate to produce a poly(p-phenylenediamine) polymer material. The addition of hydrochloric acid helps maintain the acidic environment of the reaction and promotes the catalytic effect of ammonium persulfate. This combined formula ensures the structural stability of the hydrogel while enabling the polymerization reaction to proceed efficiently within a wet and soft confined space, forming a polymer material with a dense structure and excellent performance.

[0013] Preferably, the hydrogel can distinguish active molecular monomers and polymers within its confined space through the fluorescence effect, and achieve the determination of the degree of polymerization and content of the polymer, specifically:

[0014] a) Under excitation light of a specific wavelength, p-phenylenediamine monomer and poly-p-phenylenediamine polymer each produce different fluorescence signals;

[0015] b) monitoring the progress of the polymerization reaction by changes in the intensity of the fluorescent signal;

[0016] c) Calculate the degree of polymerization and content of the polymer based on the difference in fluorescence signal intensity.

[0017] The fluorescence effect is a method for distinguishing the states of a substance by utilizing the fluorescent properties of active molecular monomers and their polymers under different states. In the present invention, the fluorescence effect of p-phenylenediamine and its polymer (poly(p-phenylenediamine)) is utilized to visually monitor the polymerization process. The monomer p-phenylenediamine and the polymer poly(p-phenylenediamine) exhibit different fluorescence intensities and wavelengths under fluorescence excitation, which enables researchers to track the progress of the polymerization reaction in real time and determine the degree of polymerization and content of the polymer. This real-time monitoring method improves the controllability and accuracy of the reaction process, helps optimize reaction conditions, and ensures the quality and performance of the material.

[0018] Preferably, the active molecule is p-phenylenediamine and the polymer is poly-p-phenylenediamine.

[0019] Paraphenylenediamine (p-phenylenediamine) is a highly active aromatic amine compound that readily polymerizes under specific conditions to form poly(p-phenylenediamine). Poly(p-phenylenediamine) is a polymer material with excellent electrical conductivity and mechanical properties, widely used in optoelectronic devices, sensors, and biomedical materials. By selecting p-phenylenediamine as the active molecule, the present invention not only ensures efficient polymer formation but also imparts excellent functional properties to the hydrogel material, such as high electrical conductivity and good mechanical strength, giving it broad potential in multiple applications.

[0020] Preferably, a method for preparing a hydrogel polymer material containing active molecules is characterized in that the method for preparing the hydrogel comprises the following steps:

[0021] a) dissolving polyvinyl alcohol in deionized water and stirring at 90° C. to 100° C. for 1.5 to 2.5 hours;

[0022] b) adding p-phenylenediamine to the polyvinyl alcohol solution obtained in step a), and magnetically stirring for 0.5 to 1.5 hours to obtain a mixed solution;

[0023] c) freezing the mixed solution in step b) for 24 hours and thawing it for 4 hours to obtain a hydrogel containing p-phenylenediamine monomer;

[0024] d) dissolving ammonium persulfate in a hydrochloric acid aqueous solution and ultrasonicating for 3 to 7 minutes to obtain a uniformly dispersed ammonium persulfate hydrochloric acid aqueous solution;

[0025] e) adding the hydrogel obtained in step c) to the solution obtained in step d) and soaking the mixture for 0.5 to 2 hours;

[0026] f) taking out the hydrogel in step e) to obtain a poly(p-phenylenediamine) hydrogel polymerized in the soft and wet environment inside the hydrogel.

[0027] This preparation method describes in detail the hydrogel material preparation process, including the preparation of a polyvinyl alcohol solution, the addition of p-phenylenediamine, the freeze-thaw process, and the final polymerization reaction. By controlling the dissolution temperature, stirring time, and freezing temperature, the structure and properties of the hydrogel can be precisely controlled. The freeze-thaw process helps form a three-dimensional cross-linked network structure within the hydrogel, providing a stable confined space within which p-phenylenediamine can polymerize in an orderly manner, forming a compact poly(p-phenylenediamine). The final polymer exhibits excellent electrical conductivity and mechanical properties, making it suitable for the preparation of a variety of functional materials.

[0028] Preferably, the dissolution temperature of the polyvinyl alcohol is 95° C., and the stirring time is 2 hours.

[0029] Polyvinyl alcohol dissolves better at higher temperatures (such as 95°C), forming a homogeneous solution. Stirring at 95°C for two hours ensures that the polyvinyl alcohol fully dissolves and forms a stable colloidal solution with water, providing a good foundation for subsequent monomer addition and hydrogel formation. Optimizing the dissolution temperature and stirring time improves the uniformity of the solution, thereby enhancing the structure and properties of the final hydrogel.

[0030] Preferably, the freezing temperature is -20°C to -10°C.

[0031] Freezing temperature has a significant impact on the three-dimensional network structure of hydrogels. Within the freezing temperature range of -20°C to -10°C, water molecules within the hydrogel crystallize into tiny ice crystals. Upon thawing, these ice crystals disappear, leaving behind a stable porous structure. Through repeated freezing and thawing, the hydrogel's three-dimensional cross-linked network gradually forms, and the cross-linking density is effectively controlled. Optimizing the freezing temperature ensures the hydrogel's structural density and mechanical strength, ultimately resulting in a polymer material with excellent properties.

[0032] Preferably, the soaking time in step e) is 1 hour.

[0033] During polymerization, immersion time is a crucial factor in controlling polymer chain growth and crosslink density. By soaking the hydrogel in the catalytic solution for one hour, the researchers ensured that p-phenylenediamine fully polymerized within the confined space, forming highly crosslinked poly(p-phenylenediamine). This optimized immersion time resulted in the final hydrogel possessing excellent mechanical strength and electrical conductivity while minimizing the brittleness that can result from overpolymerization.

[0034] Preferably, the hydrogel is prepared by a freeze-thaw method to form a cross-linked three-dimensional network structure. The three-dimensional network structure of the hydrogel is an isotropic or anisotropic structure, and has a through-hole structure or a lamellar structure.

[0035] The freeze-thaw method is an effective method for preparing hydrogels. Through repeated freeze-thaw cycles, a highly cross-linked three-dimensional network structure forms within the hydrogel. This structure can be isotropic or anisotropic, manifesting as a continuous pore structure or a lamellar structure. The formation of this three-dimensional network not only improves the mechanical properties of the hydrogel but also imparts excellent electrical conductivity and water absorption. This structural characteristic holds great promise for applications in optical devices, sensors, and biomedical materials.

[0036] Preferably, the poly(p-phenylenediamine) hydrogel is used to prepare a conductive polymer composite material, and the polymer composite material is suitable for the fields of optical devices, sensors or biomedical materials.

[0037] Poly(p-phenylenediamine) hydrogels, due to their excellent electrical conductivity and mechanical properties, are particularly suitable for preparing conductive polymer composites. These composites can be used as conductive layers or sensing elements in optical devices, and as sensitive materials in sensors, changing their properties in response to external stimuli (such as electricity, light, and temperature). Furthermore, poly(p-phenylenediamine) materials exhibit excellent biocompatibility, making them suitable for the development of biomedical materials such as tissue engineering scaffolds and drug delivery systems. Their broad application potential demonstrates the significant innovative value of the materials described in this paper in the high-tech and biomedical fields.

[0038] The present invention provides a hydrogel polymer material containing active molecules and a preparation method thereof. It has the following beneficial effects:

[0039] 1. This invention pioneered the use of the fluorescence effect of active molecules and their polymers, combined with the aggregation-inducing effect accompanying the polymerization process, to achieve real-time monitoring and visualization of the polymerization process of active molecules within the soft confined space of the hydrogel. This method provides a means for the first time to directly observe the dynamics of active small molecule polymerization reactions, accurately tracking microstructural changes during polymer formation, and significantly improving the understanding of the polymerization reaction mechanism. Through this visualization technology, researchers can better analyze and optimize the structure and properties of hydrogel materials, providing strong technical support for the customized design of polymer materials.

[0040] 2. The present invention effectively regulates the polymerization process by polymerizing active small molecules within the soft, confined space of the hydrogel, utilizing the unique environment provided by the hydrogel's three-dimensional network structure (e.g., isotropic or anisotropic structure). This confined space can control the diffusion and arrangement of active small molecules, thereby precisely adjusting the polymer's microstructure, such as chain length and intermolecular arrangement. Compared to traditional open-space polymerization, the present invention achieves detailed control of polymerization kinetics within a confined space, greatly expanding the range of performance control for hydrogel materials in various applications.

[0041] 3. By utilizing the confined space within the hydrogel, the present invention can guide the orderly polymerization of active small molecules to form a polymer material with excellent mechanical and conductive properties. By precisely controlling polymerization conditions, such as temperature, time, and solvent conditions, the molecular chain structure and crosslink density of the polymer are effectively regulated. This precise structural regulation ensures that the final polymer material not only has an ideal molecular structure at the microscopic level, but also exhibits higher strength, toughness, and functionality in terms of macroscopic performance. In particular, by selecting different types of active small molecules and polymerization conditions, the optical, electrical, and mechanical properties of the material can be further optimized to better meet the needs of specific applications.

[0042] 4. The poly(p-phenylenediamine) hydrogel material prepared by the present invention, with its excellent electrical conductivity and mechanical properties, shows broad application prospects in fields such as optical devices, sensors, and biomedical materials. This hydrogel-based polymer material can maintain stable physical and chemical properties even in harsh operating environments, ensuring the material's reliability and durability in practical applications. Furthermore, the material prepared by the present invention exhibits excellent biocompatibility, electrical conductivity, and structural stability, meeting the practical needs of various high-performance materials and promoting the widespread application of hydrogel materials in cutting-edge scientific fields.

[0043] 5. The hydrogel preparation method used in the present invention forms a cross-linked three-dimensional network structure through a freeze-thaw process. This method is simple, easy to operate, and suitable for large-scale industrial production. By precisely controlling the dissolution temperature, freezing conditions, and solution composition ratio, a polymer material with stable performance and controllable structure can be rapidly prepared. Compared with traditional complex chemical synthesis methods, the preparation process of the present invention not only significantly shortens the production cycle but also reduces the production cost of the material, providing an efficient and economical solution for the large-scale production of high-performance polymer composites. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 The present invention is a flow chart of a method for preparing a hydrogel polymer material containing active molecules;

[0045] Figure 2 is the fluorescence spectrum of p-phenylenediamine and poly-p-phenylenediamine;

[0046] Figure 3 This is the fluorescence spectrum of poly(p-phenylenediamine) at different polymerization times. DETAILED DESCRIPTION

[0047] The following will clearly and completely describe the technical solution of the present invention in conjunction with the accompanying drawings. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0048] Example:

[0049] Please see the attached Figure 1 -Attached Figure 3 :

[0050] Example 1: Preparation of poly(p-phenylenediamine) hydrogel

[0051] Recipe composition:

[0052] Polyvinyl alcohol: 1.25g

[0053] Deionized water: 23.75 mL

[0054] p-phenylenediamine: 2.514g

[0055] Ammonium persulfate: 5.3g

[0056] Hydrochloric acid: 10 mL

[0057] Process flow:

[0058] Prepare a polyvinyl alcohol solution: dissolve 1.25 g of polyvinyl alcohol (PVA) in 23.75 mL of deionized water and stir at 95° C. for 2 hours until the solution is completely dissolved to obtain a uniform polyvinyl alcohol solution.

[0059] Add p-phenylenediamine: add 2.514 g p-phenylenediamine (PDA) to the above polyvinyl alcohol solution and continue magnetic stirring for 1 hour to ensure that the p-phenylenediamine is evenly dispersed to form a uniform mixed solution.

[0060] Freeze-thaw treatment: The mixed solution was placed in a refrigerator, frozen for 24 hours, and then thawed for 4 hours. This freeze-thaw process was repeated three times to promote the cross-linking formation of the hydrogel and obtain a hydrogel containing p-phenylenediamine monomers.

[0061] Preparation of catalytic solution: 5.3 g of ammonium persulfate (APS) was dissolved in 10 mL of 3 M hydrochloric acid solution and treated under ultrasonic conditions for 5 minutes to obtain a uniform ammonium persulfate hydrochloric acid aqueous solution.

[0062] Polymerization reaction: Immerse the hydrogel obtained in step 3 in the catalytic solution in step 4 and react for 1 hour. After removing the hydrogel, repeatedly wash it with deionized water until the unreacted catalyst and byproducts are removed to obtain a poly(p-phenylenediamine) hydrogel.

[0063] Example Summary: This method successfully prepared a dense, high-performance poly(p-phenylenediamine) hydrogel by polymerizing p-phenylenediamine within the soft confines of the hydrogel. The hydrogel exhibited excellent mechanical strength and electrical conductivity, demonstrating the unique advantages of the hydrogel's confined space in regulating polymerization reactions.

[0064] Example 2: Effects of different freezing temperatures on hydrogel properties

[0065] Recipe composition: same as Example 1.

[0066] Process flow:

[0067] Solution preparation: prepare polyvinyl alcohol solution according to the method of Example 1, add p-phenylenediamine, and stir evenly.

[0068] Freeze-thaw treatment: The mixed solution was placed in a freezer at -10°C, -15°C, and -20°C for 24 hours each time, followed by thawing for 4 hours. This process was repeated three times to generate hydrogels with different structural properties.

[0069] Catalytic polymerization: The catalytic solution in Example 1 was used to carry out polymerization reaction to obtain poly(p-phenylenediamine) hydrogels prepared at different freezing temperatures.

[0070] Summary of Examples: Low-temperature freeze-thaw processing plays a key role in the structural formation of hydrogels. As the freezing temperature decreases, the resulting hydrogels increase in porosity, and their mechanical strength and electrical conductivity significantly improve. This demonstrates that at lower temperatures, ice crystal formation and thawing processes significantly influence the hydrogel's three-dimensional network structure, resulting in a denser and more stable cross-linked structure.

[0071] Example 3: Effect of different p-phenylenediamine concentrations on polymer properties

[0072] Recipe composition:

[0073] Polyvinyl alcohol: 1.25g

[0074] Deionized water: 23.75 mL

[0075] p-Phenylenediamine: Adjust to 5%, 7%, or 10% according to the required concentration

[0076] Ammonium persulfate: 5.3g

[0077] Hydrochloric acid: 10 mL

[0078] Process flow:

[0079] Solution preparation: prepare polyvinyl alcohol solutions containing 5%, 7%, and 10% p-phenylenediamine respectively, ensuring that p-phenylenediamine is completely dissolved and evenly distributed.

[0080] Freeze-thaw treatment: freeze-thaw treatment was performed according to the method of Example 1.

[0081] Catalytic polymerization: The polymerization reaction was carried out according to the steps of Example 1 to obtain poly(p-phenylenediamine) hydrogels at different p-phenylenediamine concentrations.

[0082] Example Summary: p-phenylenediamine concentration significantly affects the polymerization of hydrogels. As p-phenylenediamine concentration increases, the mechanical properties and electrical conductivity of the hydrogels gradually improve. This suggests that higher monomer concentrations provide sufficient material for polymer chain growth and cross-linking reactions, ultimately forming hydrogels with higher strength and superior properties.

[0083] Comparative Example:

[0084] Comparative Example 1: Comparison between open space aggregation and confined space aggregation

[0085] Experimental design:

[0086] Experimental group: According to the method of Example 1, the polymerization reaction of p-phenylenediamine was carried out in the confined space of the hydrogel.

[0087] Comparative group: In an open-cell environment (without the use of hydrogel), 2.514g of p-phenylenediamine was dissolved in 23.75mL of deionized water. 5.3g of ammonium persulfate and 10mL of 3M hydrochloric acid solution were added, stirred, and then polymerized at room temperature for 1 hour. After completion of the reaction, unreacted monomers were removed by filtration, and the resulting poly(p-phenylenediamine) material was washed with deionized water.

[0088] Experimental data:

[0089] Group Tensile strength (MPa) Porosity (%) Conductivity (S / cm) Experimental group 3.2 45 0.015 comparison group 1.8 20 0.008

[0090] Comparative experiments concluded that confined poly(p-phenylenediamine) materials exhibited significantly superior tensile strength, porosity, and conductivity compared to those polymerized in open spaces. The controlled confinement provided by the hydrogel ensured the orderly arrangement of polymer chains and a high crosslink density, significantly enhancing the overall performance of the material.

[0091] Comparative Example 2: Comparison of polymer properties at different freezing temperatures

[0092] Experimental design:

[0093] Experimental group: According to the method of Example 2, hydrogels were prepared at different freezing temperatures and polymerization reactions were carried out.

[0094] Comparative group: A polyvinyl alcohol solution containing 7% p-phenylenediamine was directly prepared at room temperature without freeze-thaw treatment, and then polymerization reaction was carried out according to the method of Example 1.

[0095] Experimental data:

[0096] Temperature conditions Tensile strength (MPa) Porosity (%) Conductivity (S / cm) -10℃ 2 35 0.012 -15℃ 2.8 40 0.014 -20℃ 3.2 45 0.015 normal temperature 1.5 25 0.01

[0097] Comparative Experimental Summary: Low-temperature treatment significantly improves the hydrogel's performance. As the freezing temperature decreases, the hydrogel's internal three-dimensional network becomes denser, leading to significant increases in tensile strength and electrical conductivity. In contrast, room-temperature treatment, lacking the freezing-induced structural regulation, results in lower porosity and mechanical properties.

[0098] Comparative Example 3: Comparison of polymer properties with different p-phenylenediamine concentrations

[0099] Experimental design:

[0100] Experimental group: According to the method of Example 3, hydrogels were prepared using solutions with different p-phenylenediamine concentrations.

[0101] Control group: using 5% p-phenylenediamine concentration, the polymerization reaction was directly carried out at room temperature without freeze-thaw treatment.

[0102] Experimental data:

[0103]

[0104] Comparative Experimental Summary: Hydrogels prepared using high concentrations of p-phenylenediamine combined with freezing exhibit superior properties, particularly in tensile strength and electrical conductivity. In contrast, low-concentration samples prepared at room temperature exhibit lower performance due to a lack of structural control.

[0105] Summarize:

[0106] Through a series of examples and comparative experiments, this paper fully demonstrates the effects of hydrogel confinement, freezing temperature control, and p-phenylenediamine concentration on polymer properties. Compared to traditional open-space polymerization, this technical solution significantly improves the structure and performance of polymer materials, fully demonstrating its application potential and technological innovation in the field of functional polymer materials. Every experimental step and process parameter is disclosed in detail, enabling researchers to reproduce and further optimize the properties of these materials.

[0107] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A hydrogel polymer material containing active molecules, characterized in that: The hydrogel is composed of the following raw materials in the following weight percentage ranges: Polyvinyl alcohol: 4.5%-6.5%, Deionized water: 85.5%-90.5%, p-phenylenediamine: 7%-10%, Ammonium persulfate: 1%-3%, Hydrochloric acid: 2%-5%.

2. The hydrogel polymer material containing active molecules according to claim 1, characterized in that: The hydrogel distinguishes active molecular monomers and polymers in its confined space through the fluorescence effect, and determines the degree of polymerization and content of the polymer, specifically: a) Under the excitation light of a specific wavelength, the p-phenylenediamine monomer and the poly-p-phenylenediamine polymer generate different fluorescence signals respectively; b) monitoring the progress of the polymerization reaction by changes in the intensity of the fluorescent signal; c) Calculate the degree of polymerization and content of the polymer based on the difference in fluorescence signal intensity.

3. The hydrogel polymer material containing active molecules according to claim 2, characterized in that: The active molecule is p-phenylenediamine, the polymer is poly-p-phenylenediamine, and the fluorescence detection is used to realize online monitoring of different polymerization stages during the polymerization reaction.

4. The method for preparing a hydrogel polymer material containing active molecules according to any one of claims 1 to 3, characterized in that: The preparation method of the hydrogel comprises the following steps: a) dissolving polyvinyl alcohol in deionized water and stirring at 90° C. to 100° C. for 1.5 to 2.5 hours; b) adding p-phenylenediamine to the polyvinyl alcohol solution obtained in step a), and stirring with a magnetic force for 0.5 to 1.5 hours to obtain a mixed solution; c) freezing the mixed solution in step b) for 24 hours and thawing it for 4 hours to obtain a hydrogel containing p-phenylenediamine monomer; d) dissolving ammonium persulfate in a hydrochloric acid aqueous solution, and ultrasonicating for 3 to 7 minutes to obtain a uniformly dispersed ammonium persulfate hydrochloric acid aqueous solution; e) adding the hydrogel prepared in step c) into the solution obtained in step d) and soaking the mixture for 0.5 to 2 hours; f) taking out the hydrogel in step e) to obtain a poly(p-phenylenediamine) hydrogel polymerized in the soft and wet environment inside the hydrogel.

5. The method for preparing a hydrogel polymer material containing active molecules according to claim 4, characterized in that: The dissolution temperature of the polyvinyl alcohol is 95° C., and the stirring time is 2 hours.

6. The method for preparing a hydrogel polymer material containing active molecules according to claim 4, characterized in that: The freezing temperature is -20°C to -10°C.

7. The method for preparing a hydrogel polymer material containing active molecules according to claim 4, characterized in that: The soaking time in step e) is 1 hour.

8. The hydrogel polymer material containing active molecules and the preparation method thereof according to claim 4, characterized in that: The hydrogel is prepared by a freeze-thaw method to form a cross-linked three-dimensional network structure. The three-dimensional network structure of the hydrogel is an isotropic or anisotropic structure and has a through-hole structure or a sheet structure.

9. The use of a hydrogel polymer material containing active molecules according to any one of claims 1 to 3, characterized in that: The poly(p-phenylenediamine) hydrogel is used for preparing a conductive polymer composite material, and the polymer composite material is suitable for the fields of optical devices, sensors or biomedical materials.

Citation Information

Cited By

  • Dandelion extract loaded SAS-PAAS hydrogel as well as preparation method and application thereof

    CN120860301A